Enhancing of Acetone Purity and Energy Efficiency in the Isopropyl Alcohol (IPA) Dehydrogenation Process Through Design Modifications, Heat Exchanger Integration Simulation, and Reactor Temperature Optimization - Cahyaningtyas, Asri Kusuma; Zakariya, Jaki; Fahrozi, Muhammad Aldi; Hazim, Muhammad Syafiq; Ariqah, Yulia Khalna (Journal of Chemical Engineering Research Progress, 2024)
Acetone is an essential ingredient in various industries whose demand continues to increase, thus requiring an efficient production method. This study aims to design an acetone production process by dehydrogenating isopropyl alcohol using Aspen HYSYS simulation and Aspen Energy Analyzer energy analysis. The simulation model was developed to enhance the purity of acetone products and improve energy efficiency by optimizing thermodynamic operating conditions. The dehydrogenation process was designed to produce acetone as the main product and hydrogen as a by-product. The basic process was then modified by integrating thermal energy and increasing the reactor operating temperature to improve energy efficiency and product purity. Simulations showed that the process modification resulted in an acetone purity of 99.76%, higher than the base process of 98.46%. In addition, energy savings in the modified process reached 40.89%, higher than the base process of 32.96%, with a reduction in carbon emissions of up to 40.88%. With these results, the modified process proved more efficient than the basic process and aligned with the research objectives. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).